Características anatomoclínicas e analise da da sobrevida da Neoplasia Intraductal Papilífera dos Ductos Biliares (IPNB) - José Eduardo Magri Júnior (2020)
Cholangiocarcinoma (CCA) is the second most common primary malignant neoplasm in the liver. Two precursor lesions are known, intraepithelial neoplasia (BilIN) and papillary bile duct intraductal neoplasia (IPNB). IPNB (polypoid type) shows a favorable prognosis compared to typical (non-polypoid) cholangiocarcinoma. However, few studies are available on IPNB in the western population. The present study evaluated the prevalence and survival of patients with IPNB undergoing surgical treatment in a Brazilian institution. Prospective data collection was performed according to the research protocol of the Service. Statistical analysis was performed using the T-Student and Fisher test and survival by the Kaplan-Meier method. There were ten polypoid cholangiocarcinoma and 38 non-polypoid cholangiocarcinoma. The median age was 69.5 years for polypoid and 60 for non-polypoid, with five (50%) women in polypoid carcinomas and 23 (60.6%) in non-polypoid carcinomas. One hundred percent of polypoid cholangiocarcinoma were invasive. Polypoid carcinoma was associated with gallstones (p = 0.022). The frequency of polypoid cholangiocarcinoma in the distal choledochal (70%) was significantly higher than intrahepatic (10%) and perihilar (20%) (p = 0.002). Angiolymphatic (p = 0.002) and perineural (p = 0.009) invasion were predominant in non-polypoid cholangiocarcinoma. Patients with polypoid carcinoma had longer survival than non-polypoid carcinoma (p <0.05). IPNBs constituted a small proportion of biliary tumors and were more frequent in the distal bile duct. These tumors were associated with a better outcome compared to nonpolypoid bile duct carcinoma. Angiolymphatic and perineural invasion were related to non-polypoid type.